Experimental effects of brief, single bouts of walking and meditation on mood profile in young adults - Meghan K. Edwards; Paul D. Loprinzi (Health Promotion Perspectives, 2018)
Background: To examine the effects of an acute bout of aerobic exercise and meditation on mood state among young adults. Methods: Participants (N= 66, mean age = 21.3 years) were randomly assigned to walk,meditate, or sit (control) for 10 minutes. Participants’ mood state was monitored before and after the intervention using the Profile of Mood States (POMS) questionnaire. Results: Significant group x time interaction effects were observed for the POMS composite scores (P=0.05). When evaluating three POMS sub scales separately (depression/dejection,anger/hostility, and fatigue/inertia), only fatigue/inertia was found to have a significant group x time effect (P=0.04). Post hoc paired t tests revealed that fatigue/inertia sub scale scores significantly decreased from baseline to post-intervention in both the exercise (P=0.03) and meditation (P<0.001) groups. However, POMS composite scores decreased significantly in the meditation group (P<0.001) but not in the exercise group (P=0.10). Conclusion: A 10-minute bout of brisk walking and meditation both improved mood state,when compared to an inactive control group. A single bout of brisk walking or meditation may offer suitable strategies to improve mood state among young adults.